(untitled) (Fiep Bulletin - online, 2014)
Increasing physical activity in young adults can significantly reduce the current epidemic of obesity and other diseases associated with immobility. Extremely favourable environment for the promotion of active and healthy lifestyle and the adoption and retention of physical exercise habits for years to come is physical education (PE) class. Therefore, the fundamental question in this study: “Is there a correlation between relations towards school and physical education class with physical exercise in their free time during the study’’? The study was conducted on female students of Faculty of Teacher Education, University of Zagreb via a questionnaire. Multiple correlation of relations with the school and PE classes with regard to engaging in sports activities in their free time showed 2 statistically significant variables (relations towards PE in elementary school and relation towards high school). Devastating results are related to leisure time physical activity.